TRANSFORMING MORAL EDUCATION THROUGH BARAZANJI ACCULTURATION IN SOCIETY BUGIS MAKASSAR - Muhammadong,; Khaerunnisa, (International Journal of Social Science, 2022)
The purpose of this research is find moral education in barazanji reading which can be transformed in the behavior of the Bugis Makassar community. This type of research is qualitative with a literature review method and is supported by primary data sourced from books by Sheikh Jakfar Albarazanji while secondary data is taken from interviews with religious leaders and community leaders. The results showed that the Bugis Makassar community was very inspired by reading barazanji because it contained an attitude of obedience, honesty, and mutual respect, so that they could be role models in their lives. In various celebrations, the reading of barazanji becomes the main reference because it contains praises, prayers, and prayers that can be transformed into moral education according to the current context so that there will be a revolution of views. Reading barazanji has become acculturation because it is in line with Islamic teachings so that people's enthusiasm is very high to develop their culture because it does not contradict their belief in strengthening their belief. The enthusiasm for developing barazanji is based on the compatibility between local cultures and religious fanaticism in South Sulawesi so that the community can be united.